DIGITAL CTPS (WORK RECORD BOOKLET): the implementation challenges in private companies in the region of São Carlos-SP - da Cunha, Luana Carolina Bonavina; do Nascimento, Vitória Rodrigues; Dias, Andreza Silva (Revista Interface Tecnológica, 2023)
Digital documents are more present in the lives of Brazilians, among them the digital CTPS (work record booklet) that has extreme importance in the working life of individuals and, therefore, must have its implementation expanded to make life easier for both the employee and the employer. However, there are situations that hinder its use. The current article presents an analysis of the challenges that the implementation of the digital CTPS (work record booklet) has brought to private companies in the region of São Carlos-SP, as well as the difficulties and obstacles that workers have encountered to use and have access to this document. The method used in the research was that of data survey, with two questionnaires sent and answered digitally, one of them aimed at workers in general and the other exclusively for employees of private companies who work within the Personnel Department and People Management. The results obtained by the research with the workers point out that people under 35 have demonstrated easier understanding of information, access and use of the digital CTPS, and more than 60% of the interviewees feel secure in using it. The respondents from the Personnel Department, on the other hand, affirm that private companies face some difficulties in relation to employees who have low literacy, technological knowledge and even internet, and that these workers cannot understand the need or have adequate equipment to download the necessary application. Thus, despite the difficulties, the gain in time and efficiency favors the use of the digital document.
Keywords: Labor and Social Security Card; Digital CTPS (work record booklet); Human Resources; Information Technology